Solar blind photodetector based on epitaxial zinc doped Ga2O3 thin film (Phys. Status Solidi A 5∕2017). Issue 5 (May 2017) - Alema, Fikadu; Hertog, Brian; Ledyaev, Oleg; Volovik, Dmitry; Thoma, Grant; Miller, Ross; Osinsky, Andrei; Mukhopadhyay, Partha; Bakhshi, Sara; Ali, Haider; Schoenfeld, Winston V.
Abstract : Solar blind UV photodetectors (SBPs) with a cutoff wavelength < 290 nm are of great interest for a variety of military and civilian applications. Previously, Mgx Zn1‐x O and Alx Ga1−x N alloys have been widely investigated for these applications. However, increasing the content of Mg (x > 0.37) or Al (x > 0.45) to achieve true solar blindness is accompanied, respectively, by phase segregation in MgZnO or film quality deterioration in AlGaN. An alternative material which is naturally suitable not only for solar blind detection but also for realizing true solar blindness is β‐Ga2 O3 . Its wide bandgap (∼ 4.9 eV) and suitability for growth by epitaxial deposition systems make it an excellent candidate for SBPs. Here, Alema etal. (article No.201600688 ) grew doped (Zn) and undoped β‐Ga2 O3 epitaxial films using MOCVD and fabricated the films into MSM photodetectors. The Zn doped β‐Ga2 O3 detectors showed a peak responsivity of 210 A/W with a rejection ratio of 5x10 4 . The results provide a roadmap towards achieving high responsivity SBPs with strong selectivity in the solar blind spectral window. The cover page shows a schematic illustration of MSM photodetectors fabricated from undoped and Zn doped β‐Ga2 O3 along with their I–V characteristics, and a response spectra with and without annealing.